The role of patients and their relatives in ‘speaking up’ about their own safety – a qualitative study of acute illness - Rainey, Helen (Health Expect, 2013)
BACKGROUND: Poor recognition of and response to acute illness in hospitalized patients continues to cause significant harm despite the implementation of safety strategies such as early warning scores. Patients and their relatives may be able to contribute to their own safety by speaking up about changes in condition, but little is known about the factors that influence this. This study examined the experiences and views of patients and their relatives to determine the potential for involvement in promoting their own safety. METHODS: This data set is drawn from a wider ethnographic study of the management of the acutely ill patient in hospital. Thirteen patients and seven relatives from two medical settings in two UK NHS Trusts were interviewed. Thematic analysis identified factors likely to influence patients' and their relatives' ability to contribute to the management of deterioration. RESULTS: All patients interviewed had experienced their acute illness within the context of a long‐term health problem. Speaking up was influenced by the ability to recognize changes in clinical condition, self‐monitoring, confidence and trust, and culture and system of health care. When patients or relatives did raise concerns, health‐care staff had a mediating effect on their comfort with and the effectiveness of speaking up. IMPLICATIONS: Safety strategies based on patient involvement must take account of the complexities of acute illness. Those that promote partnership may be more acceptable to patients, their families and staff than those that promote challenging behaviour and may ultimately prove to be most safe and effective.